Antibacterial activity profile of miramistin in in vitro and in vivo models. (May 2020) - Agafonova, Mariya N.; Kazakova, Renata R.; Lubina, Anna P.; Zeldi, Marina I.; Nikitina, Elena V.; Balakin, Konstantin V.; Shtyrlin, Yurii G.
Abstract: Background: Miramistin is a widely used antiseptic, disinfectant and preservative, and one of the most popular antimicrobial agents on pharmaceutical market of the Russian Federation (http://www.dsm.ru/en/news/385/ ). However, there is a lack of reported systematic data on antibacterial efficacy of this agent obtained in accordance with the international standards. Aim: This paper represents a systematic study of antibacterial properties of miramistin. Another objective of this work is to evaluate and compare the exploratory performance of in vitro and in vivo protocols of antiseptics' efficacy testing using miramistin as the reference antiseptic. Methods: Antibacterial activity of 0.1% and 0.2% aqueous solutions of miramistin against two museum strains of S. aureus (ATCC 209p) and E. coli (CDC F-50) was studied. Three standard in vitro laboratory tests (microdilution test, suspension test, and metal surface test), and one in vivo test (on rat's skin) were used. The study was conducted in accordance with the international regulatory documents. Results: Miramistin showed high bactericidal activity against the studied bacterial pathogens in the standard in vitro tests. Thus, in the microdilution test it showed expressed activity against S. aureus (MIC 8 μg/ml, MBC 16 μg/ml) and E. coli (MIC 32 μg/ml, MBC 128 μg/ml). In the suspension test, miramistin decreased the amount of colony forming units by at least 6 log10 units for S. aureus, and by at least 4.5 log10 units for E. coli . Transition to the metal surface test led to significant decrease of antibacterial activity by 1–3 log10 units as compared to the suspension test. Further dramatic reduction of antiseptic activity (by 3–4 log10 units) was observed in in vivo rat skin test. Addition of a protein contaminant (bovine serum albumin) led to a general decrease in the effectiveness of miramistin against the test pathogens (typically, by 1–2 log10 units). An interesting effect of exposure time-dependent reversal of miramistin's specificity to the studied Gram-positive S. aureus and the Gram-negative E. coli organisms was observed in the metal surface test. Conclusions: The results of this work provide systematic data on antibacterial efficacy of miramistin. They also underscore the need in relevant in vivo models for evaluation of antiseptics' efficacy. While the existing in vitro methods can be successfully applied at the discovery stages, it is necessary to use more realistic in vivo models at more advanced development stages. The observed selectivity reversal effect should be taken into account when carrying out the antiseptics' efficacy testing and surface disinfection procedures. Highlights: The data indicate bactericidal activity of miramistin against S.aureus (ATCC209p™) and E.coli (CDC F-50™) in vitro . Miramistin demonstrated decreasing microbicidal activity in vitro on metal surface, in comparison with suspension test. Antiseptic activity of miramistin was studied on S. aureus (ATCC209p™) and E coli (CDC F-50™) in vivo on rat skin surface.